Influence of Soilless and Soil-based nursery media on emergence and early seedling growth of Pawpaw (Carica papaya L.) (Agriculture, Food, and Natural Resources Journal, 2025)
Providing alternative sources of nursery media compositions is important to reduce soil mining which causes soil erosion, land degradation and nutrient leaching. This study evaluated soil-based and soilless-based nursery media on emergence, early growth, and dry matter accumulation of pawpaw seedlings for two cropping seasons. Materials utilized for the nursery media were topsoil (TS), poultry manure (PM), river sand (RS), sawdust (SD) and rice husk (RH). Eight nursery media were composted and evaluated, namely TS+PM+RS (3:2:1), TS+PM+RS (1:2:3), RS+PM+SD (3:2:1), RS+PM+SD (1:2:3), RH+PM+SD (1:1:1), topsoil (100%), RH+PM (3:1) and SD+PM (3:1). These were laid in a completely randomized design in five replications. The findings revealed that the nursery media had significant (P